Metode Clustering K-Means Pada Penjualan Handphone - Risnayanti, Risnayanti; Mughaffir, Mughaffir (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
Cell phone sales are an important part of the fast-growing technology industry. With the diversity of models and increasing consumer preferences, careful market analysis is becoming increasingly important. The aim of this research is to find relevant market segments and purchasing patterns. The research method uses K-Means clustering analysis by combining sales data with various attributes, such as brand, price, and technical specifications. The research was conducted for months at a mobile phone store in Pinrang city. The results of the research found that the K-Means clustering method managed to identify different purchases and market segments in mobile phone sales because it could provide specific features, such as preference for a particular brand, lower prices, or specific technical features to improve marketing and consumer satisfaction.